The Empathy Advantage Kepemimpinan Pelayan sebagai Kunci Loyalitas Pelanggan Sebagai Kerangka Good Corporate Governance - Lubis, Syahrizal Efendi; Hasibuan, Rosmidah (Jurnal Manajemen Akuntansi (JUMSI), 2025)
This study aims to examine the influence of Servant Leadership and Empathy Advantage on customer loyalty as a framework of Good Corporate Governance in consumers Eiger Rantau Prapat Store, North Sumatra. Using a quantitative approach with 97 respondents, data were collected through questionnaires and observations, and then analyzed by multiple linear regression. The results showed that Servant Leadership (p-value 0.009; coefficient 1.021) and Empathy Advantage (p-value 0.005; coefficient 0.521) had a positive and significant effect on customer loyalty. However, the moderating effect of the interaction of the two is not significant (p-value 0.532), so they work independently. Simultaneously, both variables explained 44.6% variation in customer loyalty. These findings indicate the importance of establishing two parallel strategies, namely the development of empathic capacity of leaders and the implementation of servant leadership systems, to increase customer loyalty in a sustainable manner.